Prevalence and diagnostic yield of investigating t wave inversion in a large unselected pre-participation cohort of young Asian males. (14th October 2021) - Ho, W H H; Lim, D Y Z; Thiagarajan, N; Wang, H; Loo, W T W; Sng, G G R; Shen, X; Sia, C H; Tan, B Y Q; Lim, H Y; Wang, L K; Chow, W; et al.
Abstract: Background/Introduction: T wave inversion (TWI) is a potentially abnormal finding on pre-participation screening electrocardiography (ECG), as it may suggest an underlying cardiomyopathy that should be risk stratified appropriately to minimise the risk of sports-related sudden cardiac death. Existing international guidelines prescribe criteria for investigating TWI in athletes. However, it is not established if these criteria can be extrapolated to screening unselected individuals. There is also evidence recommending against investigating specific patterns of anterior TWI in certain subsets of athletes due to low diagnostic yield; whether these exemptions may apply to non-athletes is uncertain. Given the importance of physical activity for primary prevention of cardiovascular disease in the general population, more evidence to guide pre-participation ECG screening of unselected individuals is needed. Purpose: Firstly, to determine the epidemiology of abnormal TWI in a large unselected pre-participation cohort of young males of predominantly Asian ethnicity. Secondly, to determine the diagnostic yield of an echocardiography-guided approach to investigating individuals with abnormal TWI for a cardiomyopathy. Methods: All individuals who attended a national centre for pre-enlistment cardiac screening over 39 months from 2017 were examined. Demographic data, anthropometric data and standardised physical fitness test scores were collected. Resting 12-lead ECG was performed for all individuals. Those with abnormal TWI, defined as a negatively deflected T wave of at least 0.1 mV amplitude in two contiguous leads, were referred to tertiary centres for echocardiography. Results: 69, 714 consecutive males of mean age 17.9±1.1 years were screened. 562 individuals (0.8%) displayed abnormal TWI. Better aerobic fitness, but not muscular strength, was associated with a higher prevalence of abnormal TWI in general and specifically in the anterior territory, although not beyond leads V1-V2. Aerobic fitness had no association with abnormal TWI in the inferior territory or lateral territory. Of those with abnormal TWI, 12 individuals (2.1%) were newly diagnosed with a cardiomyopathy. Significant factors associated with a cardiomyopathy diagnosis were abnormal TWI in the lateral territory, abnormal TWI in the anterior territory beyond lead V2, deeper maximum TWI depth, presence of hypertension and higher body mass index. No individual presenting with TWI restricted to solely leads V1-V2 and/or two inferior leads without abnormal TWI in other contiguous leads was diagnosed with a cardiomyopathy. Conclusion: Investigating abnormal TWI in an unselected pre-participation cohort of young Asian males had a significant yield, particularly in individuals manifesting abnormal TWI in the lateral territory and the anterior territory beyond lead V2. The ECG finding of anterior TWI in an unselected population may not be as benign as that in athletic populations. Funding Acknowledgement: Type of funding sources: None.